Monetary policy and risk taking - Ignazio Angeloni; Ester Faia; Marco Lo Duca (Goethe University Frankfurt, SAFE - Sustainable Architecture for Finance in Europe, 2013)
We assess the effects of monetary policy on bank risk to verify the existence of a risk-taking channel - monetary expansions inducing banks to assume more risk. We first present VAR evidence confirming that this channel exists and tends to concentrate on the bank funding side. Then, to rationalize this evidence we build a macro model where banks subject to runs endogenously choose their funding structure (deposits vs. capital) and risk level. A monetary expansion increases bank leverage and risk. In turn, higher bank risk in steady state increases asset price volatility and reduces equilibrium output.
urn:nbn:de:hebis:30:3-293785
Keywords: E5; G2; 330; bank runs; risk taking; monetary policy